Surpassing the Standard Quantum Limit in Force Sensing via Squeezed Light Injection in a Cavity Optomechanical System - Wang Jun; Chen Mei; Maria Clara Reyes (Yayasan Adra Karima Hubbi, 2025)
The Standard Quantum Limit (SQL) sets a fundamental barrier on the precision of force sensing due to quantum fluctuations. Surpassing this limit is crucial for advancing the sensitivity of force sensors, especially in applications like gravitational wave detection and quantum metrology. This study explores the potential of squeezed light injection into cavity optomechanical systems to surpass the SQL in force sensing. The main objective is to develop a method that enhances the precision of force measurements by leveraging quantum squeezing, thereby reducing quantum noise in one quadrature of the light field. The research employs both theoretical modeling and experimental techniques to study the effects of squeezed light on the force sensitivity of a cavity optomechanical system. The system was tested with varying squeezing levels and optomechanical coupling strengths. Force sensitivity was measured using a heterodyne detection setup, with the results compared to the SQL. The findings demonstrate that force sensitivity can indeed surpass the SQL by utilizing squeezed light, with a significant improvement in precision observed at higher squeezing levels. At 12 dB of squeezing, the system achieved a sensitivity of 3.1 × 10?¹³ N/?Hz, well below the SQL. This research confirms that squeezed light injection, combined with optimized optomechanical coupling, is a viable technique for quantum-enhanced force sensing.